Mercury Exposure in Pregnant Women Using Whitening Cosmetics and Potential Health Risks - Hasriwiani Habo Abbas; Yuliati Yuliati; Besse Rafiqah Andi Wajuanna (JURNAL INFO KESEHATAN, 2025)
Recently, women are increasingly using whitening cosmetics to beautify their skin. However, they are not aware that whitening cosmetics contain mercury. Several studies have reported high levels of mercury in skin whitening creams. Women, especially pregnant and lactating mothers, who use these creams are at risk of mercury poisoning because long-term exposure can cause permanent nerve damage, kidney disorders, fertility problems, and congenital disabilities.  This study aimed to analyze mercury exposure in pregnant women using whitening cosmetics and potential health risks. This research method is an observational analytic, cross-sectional design. The instrument is a questionnaire. Sampling was carried out at Khadijah 1 Hospital, Makassar City. The sample in this study consisted of 20 pregnant women who used whitening cosmetics, 20 who did not use whitening cosmetics and 20 samples of whitening cosmetics used by pregnant women. The cosmetic samples analyzed were the concentration of mercury contained in the cosmetics. Mercury testing was conducted at The Indonesian Institute for Public Health Laboratories, Makassar (BBLK). Data analysis using SPSS software. This result study showed that 20 cosmetics used by pregnant women were detected with mercury. The highest mercury concentration was 86.1 ppm, and the lowest was 3.5 ppm. Those registered with the Food and Drug Administration (BPOM) were 11 cosmetics, and 9 were not registered with BPOM. Statistical analysis shows a correlation between the frequency, duration, and volume of cosmetic use and mercury concentration in pregnant women's hair, namely 0.008, 0.017, and 0.032, respectively. The potential health risks experienced by pregnant women who use cosmetic whitening creams are anemia of as much as 55%, the fetus not actively moving as much as 15%, and the weight of the fetus not increasing as much as 30%. The statistical analysis of the relationship between mercury exposure and potential health risk experienced by pregnant women, with a p-value of 0.039 < p-value of 0.05. The use of whitening cosmetics in pregnant women can have an impact on the fetus in the womb. Therefore, pregnant women should not use cosmetics containing mercury during pregnancy and should increase their knowledge about the contents of cosmetics.